2021
DOI: 10.1002/hbm.25395
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter structures associated with neuroticism: A meta‐analysis of whole‐brain voxel‐based morphometry studies

Abstract: Neuroticism is major higher‐order personality trait and has been robustly associated with mental and physical health outcomes. Although a growing body of studies have identified neurostructural markers of neuroticism, the results remained highly inconsistent. To characterize robust associations between neuroticism and variations in gray matter (GM) structures, the present meta‐analysis investigated the concurrence across voxel‐based morphometry (VBM) studies using the anisotropic effect size signed differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 179 publications
(231 reference statements)
0
20
0
Order By: Relevance
“…Finally, we generated the mean map by voxelwise calculation of the random-effects mean of the data set maps, weighted by sample size, intra-data-set variability and between-data-set heterogeneity. We used the default SDM kernel size and thresholds (full width at half maximum [FWHM] = 20 mm; p = 0.005, uncorrected for false discovery rate; peak height Z = 1; cluster extent = 10 voxels) [35][36][37][38][39][40] as used in many previous studies because they have been validated to optimize sensitivity and specificity and to produce a desirable balance between type I and II error rates. 41 This FWHM kernel is intended to assign indicators of proximity to reported coordinates but not to smooth any image that is different in nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we generated the mean map by voxelwise calculation of the random-effects mean of the data set maps, weighted by sample size, intra-data-set variability and between-data-set heterogeneity. We used the default SDM kernel size and thresholds (full width at half maximum [FWHM] = 20 mm; p = 0.005, uncorrected for false discovery rate; peak height Z = 1; cluster extent = 10 voxels) [35][36][37][38][39][40] as used in many previous studies because they have been validated to optimize sensitivity and specificity and to produce a desirable balance between type I and II error rates. 41 This FWHM kernel is intended to assign indicators of proximity to reported coordinates but not to smooth any image that is different in nature.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained heterogeneous brain regions using the default SDM kernel size and thresholds described above. [35][36][37][38][39][40] We also performed Egger tests using Stata/SE 12.0 for Windows (Stata Corp. LP) to assess possible publication bias by extracting values from significant relevant peaks between patients and healthy controls. 35 A p value of less than 0.05 was considered significant.…”
Section: Analysis Of Heterogeneity and Publication Biasmentioning
confidence: 99%
“…fMRI studies have shown common neurofunctional alterations in the mPFC and ACC in cognitive or emotional processing in both GAD and MDD (17)(18)(19). Previous metaanalyses have identified altered volume in mPFC in GAD (22), MDD (26), and individuals with high neuroticism (48), a pathological meta-factor associated with GAD and MDD which share symptomatic (e.g., negative affect, worry) (4) and genetic etiologies (5). The mPFC is a key node in the default mode network (DMN), which is engaged in self-referential processing and emotion regulation including distress tolerance (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…3A ). Within the ACC, analysis was focused on its dorsal section (dACC) following meta-analyses of structural and functional neuroimaging studies that pointed towards the dACC as the most relevant ACC section in the context of emotional processing and neuroticism ( Liu et al, 2021 ; Servaas et al, 2013 ). The dACC mask was defined using the Destrieux Atlas (2009) as implemented in neurovault ( https://identifiers.org/neurovault.image:23264 ) ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Studies assessing the association between neuroticism scores and functional connectivity patterns also yielded mixed findings, including increased ( Cremers et al, 2010 ) and decreased ( Yang et al, 2020 ) connectivity of the amygdala with the dorsomedial prefrontal (dmPFC), as well as increased amygdala connectivity with the ventromedial prefrontal cortex (vmPFC) ( Silverman et al, 2019 ) and decreased connectivity with the ACC ( Cremers et al, 2010 ; Deng et al, 2019 ). Additional support for the putative role of the in neuroticism, particularly its dorsal part (dACC), stems from a recent meta-analysis demonstrating a positive relationship between dACC gray matter volume and neuroticism scores among healthy adults ( Liu et al, 2021 ). Taken together, neuroimaging literature highlighted the amygdala, hippocampus, and ACC as neural structures that may relate to neuroticism scores, though multiple inconsistences emerged, potentially implying that the association between neuroticism and limbic reactivity is dynamic and context dependent ( Servaas et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%